Prevalence and associated risk factors of abnormal Pap smear in pregnant women - Venkatesh, Meenakshi; Gopalan, Ushadevi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Mohindroo N et al, conducted a prospective study about the prevalence and risk factors associated with abnormal pap smear in pregnant women. This study is in need of the hour because carcinoma cervix is on increasing trend due to multiple sexual partners, HPV infection, and use of OCP in young women lead in increase in adenocarcinoma of cervix. Indian women face a 2.5% cumulative lifetime risk and 1.4% cumulative death risk from cervical cancer.